ANALISIS KECUKUPAN MODAL KERJA DALAM SISTEM TANGGUNG RENTENG PADA KSU SETIA BUDI WANITA MALANG - Yofa Faridah Wulansari, Meldona, (Fakultas Ekonomi, UIN Maliki Malang, 2012)
Funds used to carry out daily operational activities are called working capital. Working capital is expected to be able to return in cash to the company within a specified period through the sale of production and revenue services. In a Cooperative, the optimal working capital is also required to maximize profitability. This research aim was to measure the level of adequacy of working capital in improving the profitability of the cooperative in joint responsibility implementation. This type of research is a qualitative descriptive approach, hereinafter referred to descriptive qualitative research is by doing interviews with the management of Cooperatives and analyzing the financial statements. This research was conducted at Setia Budi Wanita Cooperative in Malang. Results indicate that working capital is owned by cooperative SBW is not fully optimal in improving profitability. This is indicated in GPM and ROA ratios that are declining. But when seen from the ratio of ROE, the cooperative has been able to maximize service revenue and sales to repay its debts. Â